Le Prince Impérial : le témoignage posthume d’un talent ignoré - Aude Nicolas (Les Cahiers de l'École du Louvre)
Famous for his tragic death in Zululand on 1 June 1879, the Prince Imperial nevertheless left behind artworks produced throughout his short life and which reveal his natural talents for drawing and sculpture. This article allows us to explore this little-known aspect of the prince, which shows that beyond the military, he was also an accomplished artist with gifts that were as precocious as they were promising.